Developing the Religious Attitudes of MTs Students Through Islamic Value Based Mathematics Learning in Statistics - Abdillah; Irvandi, Wandra; Utin Desy Susiaty (Absis: Mathematics Education Journal, 2025)
This study aims to: 1) ascertain the extent to which developing religious attitudes in MTs students is influenced by learning mathematics with Islamic values on statistical material supported by e-modules, and 2) ascertain the features of the religious attitudes of MTs students following their involvement in learning mathematics with Islamic values on statistical material supported by e-modules. This study used an experimental methodology. These findings are based on tests that researchers administered to students in classes IX A and IX B at MTs Negeri 1 Pontianak in the form of essay questions. Each class had 30 students. SPSS's independent sample t test yielded a Sig. (2-tailed) value of 0.019, where <0.05. Based on these findings, it can be said that 1) students who received instruction using e-modules on statistics that included Islamic content had higher learning outcomes for their religious views than students who received standard instruction. 2) Out of 30 students who worked on the posttest questions on religious attitudes in statistics in the experimental class, the religious attitudes of MTs students with the help of e-modules and Islamic-containing mathematics learning fall into the same category as 83.3% of students who finished classically.